Take control of syncing in Tiger - Cohen, Michael E. (Peachpit Press, 2007)
Learn how to synchronize all your data between Macs, or with mobile phones, PDAs, and iPods! Frustrated in your attempts to synchronize data between your Macs, or with other devices? Michael E. Cohen is here to help. With clear directions and a humorous touch, his 139-page Take Control of Syncing in Tiger walks you through tasks like syncing phone numbers between your Mac and mobile phone, iPod, or PDA; syncing files between your desktop and laptop Macs; and sharing Safari bookmarks and keychains between Macs. You'll learn what gear you need and the best ways to move your data between devices, whether your syncing software is built in to Tiger, works through .Mac, or comes from an independent Mac developer. Michael also explains how Apple's syncing model works under the hood, and when things don't work as expected, you'll appreciate his practical troubleshooting advice. Includes a coupon worth 50% off any syncing utility from PocketMac! Read this book to learn the answers to questions such as: Can I sync Address Book with my mobile phone? How does one best sync with a Palm these days? Is .Mac a good way to sync files between Macs? How can I most easily sync networked Macs? What should I look for if my sync doesn't work the way I expect?
Includes bibliographical references. - Print version record
Keywords: Macintosh (Computer); Operating systems (Computers); Macintosh (Ordinateur); Systèmes d'exploitation (Ordinateurs); operating systems